Pengaruh Pendidikan dan Pengalaman Bisnis terhadap Orientasi Kewirausahaan serta Dampaknya terhadap Orientasi Pasar - Salim Al Idrus; Abdussakir Abdussakir (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
This study aims to reveal the influence of education on entrepreneurial orientation, the influence of business experience on entrepreneurial orientation, the influence of education on market orientation, the influence of business experience on market orientation; and the influence of entrepreneurial orientation on market orientation. This study uses a quantitative approach with a sample of 168 Small and Medium Enterprises (SMEs) in East Java. Samples were taken using simple random sampling method, research data were taken through a questionnaire, and data analysis using SEM. The results of the study revealed that the higher the education and business experience, the higher the entrepreneurial orientation, the higher the education, business experience and entrepreneurial orientation, the higher the market orientation; and market orientation can be improved through improving education and business experience by paying attention to entrepreneurial orientation